(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Geometry is the single most influential design variable in high-efficiency air-purification devices such as cyclone and multicyclone separators. Over the last five years, advances in computational fluid dynamics (CFD) and surrogate-based multi-objective optimisation have enabled designers to lower pressure drop by 20–40 % while simultaneously raising fine-particle collection by up to 15 % without adding moving parts.